2021
DOI: 10.1088/1742-6596/1720/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Visual, Auditory, and Kinesthetic Students: How They Solve PISA-Oriented Mathematics Problems?

Abstract: Mathematical problems are given to students to train themselves in their thinking skills and to find out the level of thinking that each student has. Mathematical problem solving is influenced by the level of students’ thinking ability. The purpose of this study was to analyze students’ high-order thinking skills in solving PISA-oriented math problems in terms of learning styles. This type of research is a mix method with a Concurrent Triangulation Strategy design. The population of all students of class X SMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 11 publications
1
2
0
2
Order By: Relevance
“…This is evidenced by 6 students, and all students can make their assumptions. Students can analyze the information obtained into sentences or formulas that are more straightforward (Ishartono et al, 2021). This is in line with research conducted by Kholid, Pradana, et al (2022;) and Muzaki & Masjudin (2019) who concluded that some students can solve complex problems given by using their own reasoning and can perceive the problem from various points of view.…”
Section: Discussionsupporting
confidence: 80%
“…This is evidenced by 6 students, and all students can make their assumptions. Students can analyze the information obtained into sentences or formulas that are more straightforward (Ishartono et al, 2021). This is in line with research conducted by Kholid, Pradana, et al (2022;) and Muzaki & Masjudin (2019) who concluded that some students can solve complex problems given by using their own reasoning and can perceive the problem from various points of view.…”
Section: Discussionsupporting
confidence: 80%
“…However, the analysis performed in the present study is more detailed than these previous studies. More recently, Ishartono et al (2021) did not observe significant differences among Visual, Auditory, and Kinesthetic students' ability to solve PISA math problems. In addition, in the present study trimodal and tretramodal students together averaged higher academic scores than unimodal and bimodal students.…”
Section: Resultsmentioning
confidence: 94%
“…The five senses are sight, hearing, kinesthetic, smell, and taste. This study focuses only on three aspects of learning styles: visual, auditory, and kinesthetic (Ishartono et al, 2021).…”
Section: Introductionmentioning
confidence: 99%